2023
DOI: 10.17221/146/2022-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Broussonetia papyrifera leaf meal on growth performance, antioxidant capacity, and gut health status of growing rabbits

Abstract: This experiment aimed to study the effect of Broussonetia papyrifera leaf meal (BP) on the growth performance, antioxidant capacity, intestinal permeability, and caecal microbiota of growing rabbits. A total of 240 weaned Ira male rabbits were randomly divided into four groups with six replicates of 10 rabbits each. The BP was added at 0% (CON), 3.0% (BP3), 6.0% (BP6), and 9.0% (BP9). All diets were isoenergetic, isonitrogenous, and isofibrous. The feeding trial lasted for 28 days. The results showed that addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
0
1
Order By: Relevance
“…Our results are also in good agreement with those reported by Krajka‐Kuźniak (2003), who observed that TA can modulate the antioxidant enzyme activities in the liver and kidney of rats. However, no significant difference was found in antioxidation of growing rabbits with Broussonetia papyrifera (contains tannins), which was not in agreement with the previous studies (Han et al, 2023). Thus, A wide range of tannins has been extensively tested in animal diets as modulators in order to improve animals' antioxidant status and oxidative stability of their products (Besharati et al, 2022; Koleckar et al, 2008).…”
Section: Discussioncontrasting
confidence: 83%
“…Our results are also in good agreement with those reported by Krajka‐Kuźniak (2003), who observed that TA can modulate the antioxidant enzyme activities in the liver and kidney of rats. However, no significant difference was found in antioxidation of growing rabbits with Broussonetia papyrifera (contains tannins), which was not in agreement with the previous studies (Han et al, 2023). Thus, A wide range of tannins has been extensively tested in animal diets as modulators in order to improve animals' antioxidant status and oxidative stability of their products (Besharati et al, 2022; Koleckar et al, 2008).…”
Section: Discussioncontrasting
confidence: 83%